Aplikasi Gelombang Mikro sebagai Pengendali Cendawan Patogen Terbawa Benih Kedelai - Raden Sujayadi; Supyani Supyani; Edi Purwanto (Jurnal Fitopatologi Indonesia, 2017)
One of the obstacles in providing high quality soybean (Glycine max) seed is the infection of seed-borne fungal pathogens. Micro wave treatment is one of the alternative methods to control the seed-borne pathogens effectively but it needs to be further developed. This research consisted of two stages. The first stage was aimed to determine the best soybean seed moisture content in maintaining seed physiological quality after exposing to micro wave. The second stage was aimed to determine the most effective duration of micro wave exposure to reduce the rate of infection of seed-borne fungal pathogens using the best moisture content resulted from the first stage. The experiment  on seed moisture indicated that 9.20% was the best seed moisture content in maintaining the physiological quality when the seed was exposed to micro wave.  Furthermore, micro wave exposure of 60 seconds was able to control Aspergillus flavus, while the exposure of  80 seconds was able to control Fusarium sp., Curvularia sp., and A. niger.